2003
DOI: 10.1002/art.11303
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a key role of leptin in osteoarthritis

Abstract: Objective. To evaluate the contribution of leptin (an adipose tissue-derived hormone) to the pathophysiology of osteoarthritis (OA), by determining the level of leptin in both synovial fluid (SF) and cartilage specimens obtained from human joints. We also investigated the effect of leptin on cartilage, using intraarticular injections of leptin in rats.Methods. Leptin levels in SF samples obtained from OA patients undergoing either knee replacement surgery or knee arthroscopy were measured by enzymelinked immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
416
2
16

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 499 publications
(457 citation statements)
references
References 64 publications
13
416
2
16
Order By: Relevance
“…Adipocytokines acting in an autocrine or paracrine manner stimulate chondrocytes in a dual way. One of the first studies on the impact of leptin on cartilage cells revealed that this peptide increases the anabolic activity of chondrocytes by inducing IGF-1 and TGF-β expression at both mRNA and protein levels [55]. However, further studies have shown contradictory results.…”
Section: Adipocytokines In Cartilage Degradationmentioning
confidence: 99%
“…Adipocytokines acting in an autocrine or paracrine manner stimulate chondrocytes in a dual way. One of the first studies on the impact of leptin on cartilage cells revealed that this peptide increases the anabolic activity of chondrocytes by inducing IGF-1 and TGF-β expression at both mRNA and protein levels [55]. However, further studies have shown contradictory results.…”
Section: Adipocytokines In Cartilage Degradationmentioning
confidence: 99%
“…The localised effect of TGF-β and IGF-1 may be linked to an abnormal response to leptin by OA subchondral bone osteoblasts. This may occur as the expression of leptin stimulates TGF-β and IGF-1 in joint tissues [73].…”
Section: Igf and Tgf-β1mentioning
confidence: 99%
“…Otero and colleagues showed that costimulation of chondrocytes with leptin and IL-1 or interferon increased the expression of inducible nitric oxide synthase and increased nitric oxide production, thus mediating down-regulation of matrix synthesis and up-regulation of MMP activity (20). In contrast, leptin has anabolic effects in cartilage in that it stimulates 2 growth factors, transforming growth factor ␤ and insulin-like growth factor 1 (21). Thus, in cartilage, the question is whether leptin is pro-degenerative or prorepair.…”
mentioning
confidence: 99%